Influence of climatic variables on the epidemiological situation of dengue in the Ceará- Brazil (Research, Society and Development, 2021)
Dengue is a worldwide public health problem; studies show a correlation between dengue and climatic variables. Thus, this research aimed to investigate the correlation of the number of cases of patients with primary dengue symptoms (NCPPDS) with the compensated average temperature (TCA), average precipitation (PA) and compensated average relative humidity (RHCA) for the state of Ceará (2013-2018), in addition to identifying the municipalities most affected by the disease. For this analysis, institutional databases were collected and the data were compiled and processed through Statistical Package for the Social Science software. The association between climatic variables and NCPPDS was made using Pearson's correlation. It was noted that the city of Fortaleza was the municipality most affected by the disease, followed by its metropolitan region. Pearson's correlation was significant and inversely proportional between the NCPPDS and TCA in the years studied. In the NCPPDS analysis and PA, a directly proportional significant correlation was observed in the years 2013, 2017 and 2018. Regarding RHCA during the years 2013, 2015, 2017 and 2018, a directly proportional significant correlation to dengue cases was also observed. These results showed that precipitation and humidity directly influenced the number of dengue cases in the state of Ceará, and in accordance with studies in other Brazilian regions, these findings represent a general picture for dengue spreading.